A multisensory, multicognitive approach to teaching pronunciation - Odisho, Edward Y. (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
The Multisensory, Multicognitive Approach (MMA) introduced in this paper is premised on the belief that the seat of language is in the brain prior to its physical manifestation in the form of speech being in the mouth. Hence, in teaching pronunciation, the identity of speech as a cognitive entity prior to being a physical one should be seriously considered in relevant language learning and teaching situations – more so in L2 situations than in L1. The traditional assumption that the ideal and the exclusive sensory modality of teaching pronunciation is the auditory modality is no longer acceptable because a holistic view of speech – in production, transmission and perception – manifests itself not only via the auditory sensory modality, but also equally significantly via the visual and tactile-kinesthetic sensory modalities. It is due to this fact that MMA is described as multisensory, a fact that determines the diversified auditory, visual and tactile-kinesthetic implementational techniques needed for effective and efficient teaching of pronunciation especially to adults. Equally importantly, the multicognitive nature of MMA requires the manipulation of diversified cognitive processes in the form of thinking, associating, analyzing, synthesizing, comparing, contrasting etc… for implementation. According to MMA, the teaching of pronunciation becomes more of a multi- faceted educational process than a mere repeat-after-me mechanical parroting of speech sounds. Such an approach requires more effort on the part of the instructor and learner and a stronger collaboration between them through the diversification of teaching and learning styles, respectively. Certainly, MMA requires more time to implement in classroom situations, but the time spent is worth it. MMA is no longer a single technique or drill that tackles one sound at a time; instead, it is a joint selection of cognitive and sensory techniques that are applied concurrently to facilitate the L2/FL mastery in a creative and generative manner similar to the process of child language acquisition.